Edukasi Buah Nanas untuk Mengatasi Dismenorea - Safitri, Safitri; Hayati, Fatihatul (3031-8572, 2023)
Adolescence is a period of change in secondary physical and sexual growth, one of which is menstruation. The prevalence of dysmenorrhea in Indonesia reaches 98.8% in adolescents. Dysmenorrhea has a direct, negative impact on the quality of life of adolescents. Non-pharmacological therapy of pineapple fruit contains bromelain enzymes which provide analgesic and anti-inflammatory effects to relieve dysmenorrhea. Muaro Jambi Regency, to be precise in Sungai Gelam Subdistrict, Tangkit Baru Village, is a pineapple center area. MAN 1 Muaro Jambi is an educational unit with an MA level located in Sungai Gelam District and in the working area of the Tangkit Health Center, Muaro Jambi Regency. Preliminary study, 80% of young women experience dysmenorrhea and 100% of young women do not know the benefits and how to process pineapple to overcome dysmenorrhea. One way to increase health knowledge is by providing education. This community service activity was carried out for 20 adolescent girls at MAN 1 Sungai Gelam in January 2023. The expected outcome is an increase in knowledge between before and after being given education. The method used is education using e-booklets. Knowledge is assessed through the results of filling out a questionnaire with a one group pretest and posttest design approach. The results of the dedication showed an increase in knowledge after being given education by 62.7%, so that young women can utilize local plants in overcoming dysmenorrhea.Â